Immunotherapy for Asthma - Eremija, Jelena; Carr, Tara F. (Seminars in Respiratory and Critical Care Medicine, 2022)
Asthma represents one of the biggest global health concerns with increasing prevalence and influence on global health. Several distinct asthma phenotypes have been identified with one of the most common, earliest recognized, and described being the allergic asthma phenotype, in which allergens trigger asthma through mechanisms involving allergen-specific immunoglobulin E (IgE). Allergen-specific immunotherapy (AIT), in the forms of subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT), has been used for many decades as a tool for reducing IgE-mediated sensitization and controlling symptoms of allergic disease, most commonly for allergic rhinitis, and it remains the only currently available disease modifying therapy in atopic patients. AIT has been studied for use in mild to moderate allergic asthma. While the data are often inconsistent, and utilize a multitude of different methods, antigens, and outcome measures, in general, AIT may have several beneficial effects on asthma disease control, quality of life, and requirement for medication. These benefits are notable when immunotherapy is used as an adjunct to pharmacologic treatment in carefully selected and monitored patients with mild to moderate persistent asthma. Patients with severe asthma are excluded from these trials. Importantly, patients with asthma, and in particular severe asthma, may have a higher rate of systemic adverse reactions to SCIT, including anaphylaxis; however, these events are overall rare. Future research in the area is needed to definitively assess the benefit of SCIT and SLIT for patients with asthma, comparing outcomes with different methods, addressing the role of AIT in severe asthma, significance of multiallergen AIT in allergic asthma, and safety concerns in asthma.
Keywords: asthma; allergic asthma; asthma management; allergen-specific immunotherapy; subcutaneous immunotherapy; sublingual immunotherapy